2007
DOI: 10.1073/pnas.0609888104
|View full text |Cite
|
Sign up to set email alerts
|

Real-time footprinting of DNA in the first kinetically significant intermediate in open complex formation by Escherichia coli RNA polymerase

Abstract: initiation ͉ transcription ͉ wrapping ͉ kinetics S pecific transcription initiation by Escherichia coli RNA polymerase (RNAP: core subunit composition ␣ 2 ␤␤Ј ϩ 70 ϭ holoenzyme) at promoter sequences is determined by recognition of DNA (Ϫ10 and Ϫ35 hexamers) upstream of the start site (ϩ1) by the specificity subunit 70 . Subsequent to binding, a series of large-scale conformational changes in both RNAP and promoter DNA create the initiation-competent open complex (RP o ) (1). During these steps, the multisubun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
197
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(211 citation statements)
references
References 39 publications
13
197
1
Order By: Relevance
“…In the WT λP R RPo, the NT strand T residues −10, −4, −3, and +2 were accessible to modification (Fig. 2B), consistent with previous studies (5). A different pattern was observed in the complex formed with the ΔGL RNAP: Although the −10 and +2 residues were as sensitive to modification as in the WT complex, the −4 and −3 residues were significantly protected (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the WT λP R RPo, the NT strand T residues −10, −4, −3, and +2 were accessible to modification (Fig. 2B), consistent with previous studies (5). A different pattern was observed in the complex formed with the ΔGL RNAP: Although the −10 and +2 residues were as sensitive to modification as in the WT complex, the −4 and −3 residues were significantly protected (Fig.…”
Section: Resultssupporting
confidence: 88%
“…1), has been identified as an element that restricts the entry of the duplex promoter DNA into the narrow active site cleft (4), allowing only a single strand of DNA to pass through. This model posited that the DNA stands must separate outside the cleft before entry into RNAP, whereas footprinting studies demonstrated that the promoter DNA enters the active site cleft before it is opened (5). This controversy was a subject of an intense debate until a recent study revealed that the width of the RNAP cleft varies in solution and potentially is able to accommodate the duplex DNA (6).…”
mentioning
confidence: 99%
“…The conversion of the initial closed P c complex to the initiation-ready P o complex is a multi-step process. At the λP R promoter, a competitor-resistant closed complex is a significantly accumulating kinetic intermediate (Davis et al, 2007;Record et al, 1996). Whether that is the case for basal or activated transcription at the late promoter remains to be determined, so steps 3 and 4 have been lumped together.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…1 A) (12)(13)(14). The result of these changes generates a complex in which the promoter is unwound from Ϫ11 to around ϩ3, and the protection footprint extends to around ϩ25 (9,11,(15)(16)(17)(18)(19)(20)(21). In addition, RPo is normally competitor resistant, although RPo at the very strong ribosomal promoters does not follow this rule (22,23).…”
mentioning
confidence: 99%
“…In addition, structures of , core polymerase, and holoenzyme from thermophilic bacteria (4,(24)(25)(26)(27)(28)(29) or portions of E. coli 70 (30,31) have provided 3D scaffolds on which to model these steps. Kinetic analyses using the promoter P R have revealed transcriptional intermediates in the pathway from RPc to 20, and 32 and references therein). Initially, the ds promoter DNA is thought to lie across the polymerase, making sequence-specific contacts with 70 and the ␣-CTDs.…”
mentioning
confidence: 99%